Effect of Nickel Doping on Electrochemical Ozone Generation of Nickel and Antimony Doped Tin Oxide Anodes - มณีโลกย์ สุปานดี; แสงสุบัน ชลธิรา (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Ozonization has been recognized as a highly effective agent for water and wastewater treatment, therefore, it has been applied for disinfection, oxidation of organic and inorganic compound, and destruction of microorganisms. Ozone can be generated by electrochemical process using the nickel and antimony doped tin oxide (NATO) catalyst. This study presents the optimal Ni content of NATO and their surface properties to correlate with ozone generation. The NATO anodes were prepared by sol-gel and dip-coating method with varying the Ni content between 0.5% and 3% with calcination temperature at 450 oC. The significant findings show that XRD pattern of all NATO anodes showed a single rutile phase, resulting Sb5+ and Ni2+ ions replaced into Sn4+ ions in the SnO2 lattice due to the ion radius. The morphology of NATO anodes demonstrated spherical shape and well disperse. Regarding the chemical oxidation state from XPS technique, the binding energies of the Sb3d3/2 peak at 540.61 eV and 541.49 eV agree with Sb3+ and Sb5+, respectively. These chemical oxidation state can drive to active sites of oxygen adsorption and ozone activity. The optimal Ni content at 1.5% on the NATO anode was obtained the maximum ozone current efficiency of 18.7% and the current density ca. 0.08 A cm-2 in 0.5 M H2SO4 with potential of 2.7V. The ozone current efficiency and current density decreased as a function of nickel content. An electrochemical oxidation rate is observed at high current densities due to production of •OH and O3.